Pelaksanaan Trias Usaha Kesehatan Sekolah di Sekolah Menengah Pertama di Wilayah Kecamatan Purwokerto Kabupaten Banyumas - Saryono,; Ramawati, Dian; Purnawan, Iwan (Jurusan Keperawatan FIKES UNSOED, 2007)
One of health promotion level form on school age is health school programs. The important of health school program are seen in health regulation Republic of Indonesia no 23 1992 ( UU 23 th, 1992), stated that school health programs were used for increasing health life of students. The outcome of school health programs is to increase student learning, growth and development optimally. The aim of this study was to know application of the three of health school programs. This study used descriptive method throughout survey at junior high school in south and west of Purwokerto regency by cluster sampling. The respondents were a student and a teacher who performing health school programs. The data showed with a distribution table of frequency. The result of this study showed that the applications of health school program about health education, health care, and environment health facilitate at 90.45%, 70.85%, and 50.89% respectively